Halloysite Nanotubes, a Multifunctional Nanovehicle for Anticancer Drug Delivery - 郭明义 王艾菲 费海姆 齐文秀 任浩 郭颖杰 朱广山 (Chinese journal of chemistry, 2012)
Targeted drug delivery systems have attracted a great deal of interest by virtue of their potential use in chemotherapy. In this study, multicomponent halloysite nanotubes （HNTs） have been evaluated as a platform to assist and direct the delivery of anticancer drug doxorubicin （DOX） into cancer cells. Folic acid （FA） and magnetite nanopar- ticles were successfully grafted onto HNTs via amide reaction whereas the drug has been introduced by capitalizing electrostatic interaction between cationic drug and anionic exterior of HNTs, which eventually leads to pH respon- sive release. The resultant DOX loaded FA-Fe304@HNTs were well characterized by transmission electron mi- croscopy （TEM）, scanning electron microscopy （SEM）, Fourier transform infrared spectroscopy （FTIR） and XRD. The clinical efficacy of the system was validated by confocal microscopy and cell cytotoxicity assay （MTT assay）. MTT assay results revealed a high biocompatibility up to a concentration of 200 μg/mL of HNTs, while, DOX loaded FA-Fe304@HNTs were markedly cytotoxic to HeLa cells. This multifunctional nanovehicle has a great po- tential for cancer diagnosis and therapy, and could further advance the clinical use of nanomedicine.